Assessment of climate change impacts on flooding in the downstream of the Dong Nai River - Thai, Tran Hong (VNU Journal of Science: Earth and Environmental Sciences, 2011)
Abstract . In recent decades, the increasing in greenhouse gas emission has caused global warming leading to many adverse changes of the environment especially the sea level rise and the hydrological regime . The Dong Nai river basin having the downstream part below the sea level is among the most vulnerable basins to climate change. Recents studies showed that the sea level in the downstream of Sai Gon - Dong Nai river basin is rising. Many cities downstream of the basin especially Ho Chi Minh city are being flooded in flow tides which seriously affect the socio-economic development. Thus, research on the future impacts of climate change on flooding in this area is of vital importance. This paper applied the HydroGIS modeling package to predict the flooding levels in the Dong Nai river basin for the period from 2020 – 2100 taking into account the impact of climate change. Inundation maps were developed based on three climate change scenarios namely B1, B2 and A1FI and different sea level rise values (e.g. 15, 25, 50, 75 and 100cm). These maps together with comprehensive analysis on the trend and extent of flooding will assist decision makers in developing mitigation measures coping with flooding in the river basin. Keywords: Climate change, flooding, Dong Nai river, HydroGIS.